Teachers resilence : coping strategies of primary school teachers with multi-grade classes at Glen Cowie Circuit, Limpopo Province South Africa - Tlaka, Manchini Ishmael (My University, 2021)
The purpose of this study was to explore the coping strategies of primary school teachers in their multi-grade classes at Glen Cowie circuit. This exploratory case study addresses the coping strategies that rural primary school teachers use in curriculum delivery. Data was generated through semi-structured interviews, observations and document analysis. This study revealed various challenges teachers experience and the coping strategies that teachers employ in dealing with challenges. A qualitative research approach was adopted in the study with the intention of finding as much detail as possible using a case study. Participants in this study were teachers who teach multi-grade classes in their rural schools in the Glen Cowie circuit in Limpopo. The investigation revealed that teachers did not have the necessary skills and expertise to teach multi-grade classes. It was also revealed that teachers were not trained to teach in multi-grade classes and they had to use individual strategies to cope with the contradictory conditions they found themselves in. The investigation concluded that the teachers in those multi-grade classes were qualified and had teaching experience, but they were not prepared to teach multi-grade classes in general. It proved that teachers remained resilient by applying varied strategies such as problem solving, goal setting, extra curriculum lessons and maintaining work-life balance to ensure that teaching and learning occurs
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2021
Keywords: Coping strategies; School teacher; Glen Cowie circuit; Multi-grade; Teachers; Primary school teachers -- South Africa -- Limpopo; Elementary school teachers -- Self-rating of